IL‐6/Smad2 signaling mediates acute kidney injury and regeneration in a murine model of neonatal hyperoxia. Issue 5 (5th February 2019) - Mohr, Jasmine; Voggel, Jenny; Vohlen, Christina; Dinger, Katharina; Dafinger, Claudia; Fink, Gregor; Göbel, Heike; Liebau, Max C.; Dötsch, Jörg; Alcazar, Miguel A. Alejandre
ABSTRACT: Prematurity is linked to incomplete nephrogenesis and risk of chronic kidney diseases (CKDs). Oxygen is life‐saving in that context but induces injury in numerous organs. Here, we studied the structural and functional impact of hyperoxia on renal injury and its IL‐6 dependency. Newborn wild‐type (WT) and IL‐6 knockout (IL‐6 −/− ) mice were exposed to 85% O2 for 28 d, followed by room air until postnatal d (P) 70. Controls were in room air throughout life. At P28, hyperoxia reduced estimated kidney cortex area (KCA) in WT; at P70, KCA was greater, number of glomeruli was fewer, fractional potassium excretion was higher, and glomerular filtration rate was slightly lower than in controls. IL‐6 −/− mice were protected from these changes after hyperoxia. Mechanistically, the acute renal injury phase (P28) showed in WT but not in IL‐6 −/− mice an activation of IL‐6 (signal transducer and activator of transcription 3) and TGF‐β [mothers against decapentaplegic homolog (Smad)2] signaling, increased inflammatory markers, disrupted mitochondrial biogenesis, and reduced tubular proliferation. Regenerative phase at P70 was characterized by tubular proliferation in WT but not in IL‐6 −/− mice. These data demonstrate that hyperoxia increases the risk of CKD through a novel IL‐6–Smad2 axis. The amenability of these pathways to pharmacological approaches may offer new avenues to protect premature infants from CKD.—Mohr, J., Voggel, J., Vohlen, C., Dinger, K., Dafinger, C., Fink, G., Göbel, H., Liebau, M. C., Dötsch, J., Alejandre Alcazar, M. A. IL‐6/Smad2 signaling mediates acute kidney injury and regeneration in a murine model of neonatal hyperoxia. FASEB J. 33, 5887–5902 (2019). www.fasebj.org